Family Support System as an Effort to Optimize Coping Mechanism of Preschool Children During Hospitalization - M. Hasinuddin; Ulva Noviana; Fitriah Fitriah (Universitas Airlangga, 2019)
Introduction: The condition of the child during hospitalisation can experience stress due to environmental changes. Child coping mechanism is very supportive of the adaptation process. The purpose of this study was to analyze the effect of family support system on coping mechanisms during hospitalisation. Methods: It was quasi-experimental with pre-test post-test with control group design. The study population was preschool children who were treated in the Hospital of Bangkalan, East Java Province, Indonesia. Total sample was 60 respondents in treatment and control group and obtained consecutive sampling. The variables were family support system and coping mechanism. Data collection used Children’s Coping Behavior questionnaire and tested by paired t-test. Results: The treatment group showed the coping mechanism was mostly maladaptive (mean=34.07) and after the intervention most of them had adaptive coping (mean=46.87). Whereas in the control group before the intervention, the coping mechanism was mostly maladaptive (mean=36.22) and after the intervention most of the coping groups had maladaptive coping (mean=36.74). Conclusion: Family support systems play an important role in improving the adaptive coping of preschool children during hospitalisation. Nurses should maximise family support as a strategy in interacting with children to enhance coping mechanisms to reduce the stress of hospitalisation.